Customer Relationship Management (CRM) Strategy Analysis in Enhancing Customer Loyalty in Digital Business - Ni Nyoman Suarniki; Rika Sylvia; Dewi Setiawati (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2026)
This study examines the role of Customer Relationship Management (CRM) strategies in enhancing customer loyalty in digital business environments, where intense competition and low switching costs require companies to actively build and maintain customer relationships. The research employs a quantitative approach with an explanatory design, involving respondents who actively use digital platforms. Data were collected through structured questionnaires and analyzed using multiple linear regression to determine the influence of CRM components on customer loyalty. The findings reveal that personalization, integrated communication, digital experience, and technology utilization have a positive and significant effect on customer loyalty. Among these factors, personalization and technology-driven CRM strategies are identified as the most influential variables, indicating the importance of data-driven decision-making and advanced digital tools in managing customer relationships. The discussion highlights that effective CRM strategies operate through a relational mechanism, where understanding customer needs leads to improved satisfaction and trust, ultimately strengthening loyalty. The study concludes that an integrated CRM strategy is essential for fostering sustainable customer loyalty and maintaining competitive advantage in digital business. These findings provide both theoretical contributions and practical implications for businesses in optimizing CRM implementation